Efecto de la intensidad eléctrica y el tiempo en la disminución de la materia orgánica y turbidez en la electrocoagulación de las aguas residuales de la ciudad universitaria UNT - Aguilar Villanueva, Juan Carlos (2018)
The objective of this research was to evaluate the effect of current intensity and time on the decrease of organic matter and turbidity in the electrocoagulation of wastewater produced in the University City of the National University of Trujillo (UNT). The residual water was charaterized and 508 mg O2/L of Oxygen Chemical Demand (DQO) and 165 Nephelometric Turbidity Unit (NTU) on average. The treatment and the analyzes were done in the laboratory of Analytic Chemistry of the Faculty of Chemical Engineering of the UNT, where a batch-monopolar electrocoagulation cell with a capacity of 3 375 mL was built, the aluminum electrodes had effective area of 146,6 cm2. The levels of the variables used were 1, 2,5 and 4 amperes (A) of current intensity and times of 15, 30 and 60 minutes. The experimental results indicated a maximum decrease in the amount of organic matter and turbidity on average of 81% and 76% respectively at 4 amps of intensity and 60 minutes